Health and the conservation of wildlife in nature - Macedo, Gabriel Carvalho de; Herrera, Heitor Miraglia; Jansen, Ana Maria; de Oliveira, Carina Elisei; Rocha, Fabiana Lopes; Porfírio, Grasiela Edith de Oliveira (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2022)
Wild populations are constantly threatened due to the global expansion of human population and consequent loss of original habitats, pollution, increased movement of people and animals, and the introduction of exotic species. In this sense, hematological, biochemical, toxicological, and parasitological studies have been used to understand the health status of many wild species. There is a difficulty in interpreting the observed values, especially concerning the assessment of physiological parameters, since factors related to the individual and the environment, as well as animal caging and the use of drugs for sedation, influence the hematological values and biochemical dosages. In this context, data on parasitism and the health of wild mammals from the Pantanal were compiled through bibliometrics and discussed in terms of the resilience and sustainability of their populations. We conclude that the scientific community should work together with an organized society to encourage the creation and application of public conservation policies to maintain biodiversity and the continuity of ecological processes.